FAMILY KIZLYAR (KIZLYAR) REGIMENT THE CAUCASIAN LINEAR COSSACK ARMY - Nikolaj Nikolaenko (Гуманитарные и юридические исследования)
The article studies the problems of formation and functioning of the Kizlyar regiment of the Caucasian Linear Cossack army. Based on the analysis of the published source a number of facts about Tersko-Semeyny and Tersko-Kizlyar Cossack armies on the eve of formation of the Caucasian Linear Cossack army is given. The process of formation of the Family Kizlyar (Kizlyar) regiment and regimental villages with the number of male population in each is considered. The location of the regimental headquarters is specified. The problems of replenishment of the Family Kizlyar (Kizlyar) regiment, the salaries of rank and file Cossacks and officers are analyzed. The composition of Kizlyar regiment from the moment of its formation and up to disbandment of the Caucasian Linear Cossack army is investigated. Based on unpublished documents of the Russian State Military Historical Archive, participation of the Cossacks of the Kizlyar Regiment in combat operations on the left flank of the Caucasian Line is considered. It is concluded, that among the Cossack villages of the Caucasian Linear Cossack Army, the villages of the Kizlyar Regiment were the smallest in number of ordinary Cossacks in them.